2013
DOI: 10.1111/j.1600-048x.2013.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

High rates of conspecific brood parasitism revealed by microsatellite analysis in a diving duck, the common pochard Aythya ferina

Abstract: Conspecific brood parasitism (CBP) is a reproductive tactic whereby a parasitic female lays its eggs into the nests of other conspecific females. Genetic‐based data on the occurrence of CBP in birds, however, is still relatively scarce. We analysed prevalence of CBP in a ground‐nesting diving duck, the common pochard Aythya ferina, using a set of 17 microsatellites. Compared to related species, our population showed a relatively high level of CBP, with 39% of genotyped pochard eggs laid parasitically and 89% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…If a parasite can lay her egg(s) in the nest of an unrelated host, she is likely to increase her expected number of offspring. But trying to lay eggs in the nest of an unknown female may fail for several reasons (Roy Nielsen et al ., , c ; Anderholm et al ., , b ; Štovíček et al ., ). A close relative may offer a safer possibility; host–parasite relatedness tended to be higher in successful than in failing goldeneye nests (Andersson & Åhlund, ).…”
Section: Causes Of Host–parasite Relatednessmentioning
confidence: 99%
“…If a parasite can lay her egg(s) in the nest of an unrelated host, she is likely to increase her expected number of offspring. But trying to lay eggs in the nest of an unknown female may fail for several reasons (Roy Nielsen et al ., , c ; Anderholm et al ., , b ; Štovíček et al ., ). A close relative may offer a safer possibility; host–parasite relatedness tended to be higher in successful than in failing goldeneye nests (Andersson & Åhlund, ).…”
Section: Causes Of Host–parasite Relatednessmentioning
confidence: 99%
“…As cervus was developed 12 years before colony , it is not surprising that the majority of the studies used the program cervus (17 of 28) to assign parentage, while three used colony , and one study used both. Several studies (seven) did not use either parentage assignment program but instead relied on methods such as comparing the genotypes of females and offspring and assigning maternity based on the occurrence of mismatches (often only at one or two loci) relative to that expected given allele frequencies, expected mutation rates, genotyping error, null alleles or allele drop‐out (e.g., Hervey et al, 2019; Šťovíček et al, 2013; Tiedemann et al, 2011). The choice to use exclusion by mismatch instead of parentage assignment may reflect a discomfort with available programs, including the limitations that we have tried to address in the present study (Anderholm et al, 2009); however, despite the appeal of simplicity, exclusion is somewhat arbitrary (Flanagan & Jones, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(often only at one or two loci) relative to that expected given allele frequencies, expected mutation rates, genotyping error, null alleles or allele drop-out (e.g., Hervey et al, 2019;Šťovíček et al, 2013;Tiedemann et al, 2011). The choice to use exclusion by mismatch instead of parentage assignment may reflect a discomfort with available programs, including the limitations that we have tried to address in the present study (Anderholm et al, 2009); however, despite the appeal of simplicity, exclusion is somewhat arbitrary (Flanagan & Jones, 2019).…”
Section: Implications For Past and Future Field Studiesmentioning
confidence: 99%
“…In this study we have two main aims. First, we wanted to test if the Eadie's MED method is reliable for detecting CBP in our study species – common pochard Aythya ferina , in which high rates of CBP has been reported (Petrželková et al , Šťovíček et al ). In order to do this, we used nests that were independently identified as parasitized or non‐parasitized based on protein fingerprinting (Andersson and Åhlund ).…”
mentioning
confidence: 99%